Linking leadership to student learning - Leithwood, Kenneth A. (John Wiley & Sons, 2011)
Linking Leadership to Student LearningLinking Leadership to Student Learning clearly shows how school leadership improves student achievement. The book is based on an ambitious five-year study on educational leadership that was sponsored by The Wallace Foundation. The authors studied 43 districts, across 9 states and 180 elementary, middle, and secondary schools. In this book, Kenneth Leithwood, Karen Seashore Louis, and their colleagues report on what they found. They examined leadership at each organizational level in the school system--classroom, school, district, community, and state. Their.